Infant high-grade gliomas comprise multiple subgroups characterized by novel targetable gene fusions and favorable outcomes - Clarke, Matthew; Karremann, Michael; Korshunov, Andrey; Jones, Barbara Christine; Sturm, Dominik; Witt, Olaf; Deimling, Andreas von; Pfister, Stefan; Sahm, Felix; Capper, David; Jones, David T. W. (Cancer discovery, 2020)
Infant high-grade gliomas appear clinically distinct from their counterparts in older children, indicating that histopathologic grading may not accurately reflect the biology of these tumors. We have collected 241 cases under 4 years of age, and carried out histologic review, methylation profiling, and custom panel, genome, or exome sequencing. After excluding tumors representing other established entities or subgroups, we identified 130 cases to be part of an "intrinsic" spectrum of disease specific to the infant population. These included those with targetable MAPK alterations, and a large proportion of remaining cases harboring gene fusions targeting ALK (n = 31), NTRK1/2/3 (n = 21), ROS1 (n = 9), and MET (n = 4) as their driving alterations, with evidence of efficacy of targeted agents in the clinic. These data strongly support the concept that infant gliomas require a change in diagnostic practice and management. SIGNIFICANCE: Infant high-grade gliomas in the cerebral hemispheres comprise novel subgroups, with a prevalence of ALK, NTRK1/2/3, ROS1, or MET gene fusions. Kinase fusion-positive tumors have better outcome and respond to targeted therapy clinically. Other subgroups have poor outcome, with fusion-negative cases possibly representing an epigenetically driven pluripotent stem cell phenotype.See related commentary by Szulzewsky and Cimino, p. 904.This article is highlighted in the In This Issue feature, p. 890.